Effect of Cyberlindnera jadinii yeast as a protein source on intestinal microbiota and butyrate levels in post-weaning piglets - Stanislav Iakhno; Özgün C. O. Umu; Ingrid M. Håkenåsen; Caroline P. Åkesson; Liv T. Mydland; Charles McL. Press; Henning Sørum; Margareth Øverland (Animal Microbiome, 2020)
Abstract Background Dietary yeast inclusions in a pig diet may drive changes both in gut bacterial composition and bacterial functional profile. This study investigated the effect of Cyberlindnera jadinii as a protein to replace 40% of the conventional proteins in a diet for weanling pigs on the microbiota in the small and large intestine, colonic short-chain fatty acid concentration, and colonic histopathology parameters. Seventy-two pigs weaned at 28 days of age were randomly assigned to either a control or a C. jadinii-based diet and followed for 2 weeks. Results Compared with the controls, higher numbers of cultivable lactic acid-producing bacteria in the small and large intestine were registered in the yeast group. Alpha and beta bacterial diversity were different between the diet groups with lower alpha-diversity and distinct bacterial composition in the large intestine in the yeast group compared with those of the controls. The large intestine microbiota in the yeast group had higher numbers of Prevotella, Mitsuokella and Selenomonas compared with those of the controls. The concentrations of colonic acetate and butyrate were higher in the controls compared with that of the yeast group. The colonic crypt depth was deeper in the control group. The gut histopathology of colonic tissues revealed no differences between the diets. The colonic crypt depth tended to be deeper with higher relative abundance of an unclassified Spirochetes, higher colonic butyrate concentration, and higher bacterial richness. The concentration of colonic butyrate was positively associated with the relative abundance of the Faecalibacterium prausnitzii, Dialister, and an unclassified amplicon of the Spirochaetaceae family in the colon. Conclusions The replacement of the conventional proteins by proteins from Cyberlindnera jadinii in a weanling pig diet reshaped the large intestine microbiota structure. The novel yeast diet appeared to be selective for Lactobacillus spp., which may represent an added value resulting from using the sustainably produced yeast protein ingredient as an alternative to conventional protein ingredients in animal diets. The large intestine bacterial composition and their metabolites may be involved in an adaptive alteration of the colonic crypts without pathological consequences.